The Protective Role of Teacher Autonomy Against Work-Family Conflict: A Cross-Generational Study of Female Junior High School Teachers in Indonesia - Gayuk Zulaika; Yusti Probowati Rahayu; Artiawati Artiawati (Universitas PGRI Yogyakarta, 2026)
Cross-generational junior high school female teachers face multi-role challenges that can trigger family conflicts and affect performance. This study aims to test teacher autonomy as a protective factor in mitigating family conflicts that have an impact on work, as well as analyzing the age difference (Generation X: 43-58 years and Generation Y: 28-42 years) as moderators. This study, involving 691 female junior high school teachers in Java, uses purposive sampling and the Teacher Autonomy Scale and the Family-Work Conflict Scale. Hierarchical regression analysis with SPSS 27.0 was used to test the hypothesis. The results showed that teacher autonomy was negatively and significantly related to family conflicts affecting work (β = -0.365; p < 0.001), with an effective contribution of 13.3%. This means that the higher teachers' autonomy, the lower the family conflicts that affect work. Age variables also contributed significantly to the decrease in conflict (ΔR² = 0.057; p < 0.001). However, the role of age moderation was not significant (ΔR² = 0.001; p = 0.474), confirming teacher autonomy as a universal buffer resource whose effectiveness does not depend on generational differences. These findings confirm that autonomy functions as a structural need, not as a function of age cohorts. Policy implications recommend the formalization of schedule flexibility and autonomy-based interventions, such as partial time flexibility and professional scheduling autonomy. This strategic step is crucial to improving the psychological well-being of female teachers and to affirming autonomy as a key instrument in family-friendly policies in the education sector. Keywords: family interferences with work conflict, teacher autonomy, female teachers, cross-generational